School Based 4-H Programming: Middle and High School Age Youth Programs - Vanessa Spero (EDIS)
All youth, regardless of age, are at risk for engaging in negative behaviors that can get them into trouble during the afterschool hours when parents and other family members are at work. Middle and high school-age youth are at an age where they can most benefit from increasing opportunities to participate in programs with a positive adult role model, gain necessary life skills, and increase their knowledge of accessible opportunities. Middle and high school programs have the potential to support graduation rates and increase post-secondary school success. This 4-page publication of the UF/IFAS Florida 4-H Youth Development Program provides strategies for success in developing these programs in your community. Written by Vanessa Spero-Swingle. https://edis.ifas.ufl.edu/4h400